PENGENDALIAN STOK DAN PREDIKSI PEMESANAN MENGGUNAKAN METODE EOQ PADA NYUUSUU SEMARANG - Fadilla Nurul Alif; Sri Eniyati (Teknik Informatika, 2021)
Stock is the most important thing in running a shop business. The right amount of stock of raw materials will be very helpful in the operation of the shop business. The shop will be able to minimize losses such as reducing the cost of maintaining the stock of raw materials, minimizing the damage to the stock of raw materials due to being stored for too long, and ensuring the quality of the stock of raw materials. The purpose of this study is to assist the shop in minimizing its losses by building a stock control website and order prediction using the EOQ method. With this website, it produces the optimal amount of stock with EOQ calculations that can be used by shops to place stock orders. The amount of stock produced is obtained from sales data from September 2019 to September 2020. The results of this study are expected to help the shop in managing the optimal amount of stock.